AHP-MAUT Dalam Sistem Pendukung Keputusan E-Wallet Terfavorit - Marlina Marlina; Wina Yusnaeni; Sucitra Sahara (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bina Insani, 2024)
E-wallets have increased in use starting from the pandemic period , everything from online shopping through Shoopee, tokopedia, etc. uses electronic money in making transactions. This is done for ease without meeting or making contact with other people. The more widespread the electronic money used, the more types offered include ShoopePay, Gopay, OVO , DANA and others. This results in problems for users in determining which brand to use and which is more effective and profitable for users. This study aims to provide a solution to which e-wallet users have the best advantage to use. In this case the researcher uses a decision support system with predetermined criteria in the form of security, availability, ease of use, additional features, cost and integration with other costs. Assessment Data can be through questionnaires with questionnaire type AHP method, and also AHP method is used to obtain consistency values and eigenvalues of each criterion and alternatives to the criteria. For the calculation of normalization using the death Method to get the value of 1 and 0 as well as the multiplication of the matrix with weights that have been previously obtained by the AHP method. The final result of determining the value is the priority value of the final result which will be the ranking of the favorite e-wallet.